Solar model independent constraints on the sterile neutrino interpretation of the Gallium Anomaly - M.C. Gonzalez-Garcia; Michele Maltoni; João Paulo Pinheiro (Physics Letters B)
We perform a global analysis of most up-to-date solar neutrino data and KamLAND reactor antineutrino data in the framework of the 3+1 sterile neutrino mixing scenario (invoked to explain the results of the Gallium source experiments) with the aim of quantifying the dependence of the (in)compatibility of the required mixing with assumptions on the initial fluxes. The analysis of solar data is performed in two alternative ways: using the flux predicted by the latest standard solar models, and in a model independent approach where the solar fluxes are also determined by the fit. The dependence on the normalization of the capture rate in the solar Gallium experiments is also quantified. Similarly, in the KamLAND analysis we consider both the case where the reactor flux normalization is assumed to be known a priori, as well as a normalization free case which relies solely on available neutrino data. Using a parameter goodness of fit test, we find that in most cases the compatibility between Gallium and solar+KamLAND data only occur at the 3σ level or higher. We also discuss the implications of enforcing better compatibility by tweaking the mechanism for the energy production in the Sun.